THE INFLUENCE LEVERAGE, PRIOR OPINION AND FINANCIAL DISTRESS ON GOING CONCERN AUDIT OPINION - Qodri, Renaldi; Kurnia Krisna Hari; Fahmi, Muhammad; Ningsih, Nurul Hutami (Jurnal Akuntansi, Keuangan, Perpajakan dan Tata Kelola Perusahaan, 2025)
The purpose of this study was to determine the effect of leverage, prior opinion and financial distress on going concern audit opinions. This type of research is associative. The data used is secondary data taken from the annual reports of BUMN companies for 2019-2022. Method, the sample used is saturated sampling, and a total of 25 companies, so the total of sample for this study was 25 companies. The data collection technique is documentation. The method of data analysis in this study is quantitative. The results of this study were assisted by the Statistical Program For Special Science (SPSS). The results show that partially Leverage has an effect on the Going Concern Audit Opinion, Prior Opinion has an insignificant effect on the Going Concern Audit Opinion and Financial Distress has an insignificant effect on the Going Concern Audit Opinion.